1985
DOI: 10.1111/j.2042-3306.1985.tb02524.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental reactivation of equid herpesvirus 1 (EHV 1) following the administration of corticosteroids

Abstract: Summary Eight ponies were experimentally infected with equid herpesvirus 1 (EHV 1) (subtype 1). All animals showed clinical and serological evidence of infection and virus was isolated from nasal swabs and leucocytes. These ponies were kept in isolation for a further three months during which time complement fixing antibody decreased at least four‐fold. Following immunosuppression with dexamethasone and prednisolone subtype 1 virus was recovered from six of the eight animals within 14 days. Five of these six p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
72
3
3

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 9 publications
(8 reference statements)
2
72
3
3
Order By: Relevance
“…The reverse is true for EHV-1 in the horse, where leukocytes were first identified as the site of latency (Edington et al, 1985(Edington et al, , 1994Welch et al, 1992), while detection in the trigeminal ganglia has shown a low frequency of neurones expressing LATs (Baxi et al, 1995) and with either no recovery or only low frequencies of infectious virus from latently infected neurones (Burrows & Goodridge, 1984 ;Edington et al, 1994 ;Slater et al, 1994). The present work is consistent with the range of variation in the predominant sites of latency that is seen between alphaherpesviruses in different hosts.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The reverse is true for EHV-1 in the horse, where leukocytes were first identified as the site of latency (Edington et al, 1985(Edington et al, , 1994Welch et al, 1992), while detection in the trigeminal ganglia has shown a low frequency of neurones expressing LATs (Baxi et al, 1995) and with either no recovery or only low frequencies of infectious virus from latently infected neurones (Burrows & Goodridge, 1984 ;Edington et al, 1994 ;Slater et al, 1994). The present work is consistent with the range of variation in the predominant sites of latency that is seen between alphaherpesviruses in different hosts.…”
Section: Discussionsupporting
confidence: 75%
“…Leukocytes also have been identified as a site of latency for EHV-1 (Edington et al, 1985(Edington et al, , 1994Welch et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent work using polymerase chain reaction and co-cultivation studies has shown that latent EHV-1 in outbred animals is always detected in lymphoid tissues in the presence of EHV-2 (for review see Edington, 1991). It is also reported that recovery of EHV-2 precedes EHV-1 when corticosteroids are used in immunosuppression (Edington et al, 1985). In contrast to previous findings (Allen & Turtinen, 1982;Staczeck et al, 1983), recent work in our laboratory has shown that EHV-I DNA cross-hybridizes significantly with EHV-2 DNA.…”
Section: Introductioncontrasting
confidence: 54%
“…Latent EHV-1 and EHV-4 infections in horse have been shown to reactivate from lymphoid tissues following the administration of corticosteroids (Edington et al, 1985;Edington et al, 1994a, b;Browning et al, 1988;Welch et al, 1992) and also by IL-2 or chorionic gonadotrophin stimulation of leukocytes (Smith et al, 1998). Borchers et al (1999) also have been able to detect latency associated transcripts of EHV-1 and EHV-4 by PCR from trigeminal ganglia of the latently infected horses.…”
Section: Discussionmentioning
confidence: 87%